Elevated somatostatin interneuron long-term potentiation minimally regulates temporoammonic plasticity in a mouse model of Fragile X Syndrome - Wilson, Max A.; Sumera, Anna; Berk, Emre; Booker, Sam A. (Frontiers in Pharmacology, 2026)
IntroductionFragile X Syndrome is a common, inherited single gene cause of intellectual disability, associated with autism, epilepsy, anxiety, and sensory disturbances. Many of these features have been attributed to cellular dysfunction leading to impaired synaptic plasticity, in particular through metabotropic glutamate and GABA receptor signalling. The function of these pathways in inhibitory interneurons has not been fully elucidated. In this study we test the hypothesis that somatostatin interneurons (SST-INs) display impaired synaptic plasticity, which leads to circuit-level plasticity deficits.MethodsWe use a combination of whole-cell and extracellular recordings in acute hippocampal brain slices prepared from adult, male wild-type and Fmr1-/y mice. ResultsWe find that long-term potentiation in SST-INs is enhanced in Fmr1-/y mice, and that this plasticity is susceptible to GABAB receptor activation. However, long-term potentiation at temporoammonic inputs to CA1 region is not impaired in Fmr1-/y mice following tetanic stimulation. We find that temporoammonic long-term potentiation is equivalently modified by metabotropic glutamate and GABA receptor pharmacology, despite changes in presynaptic function.DiscussionThese data show that while SST-IN function is impaired in Fmr1-/y mice, circuit level plasticity is maintained. This study provides new insights into the function of drugs proposed for the treatment of Fragile X Syndrome.